2023
DOI: 10.1186/s13568-023-01537-8
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genome analysis of Burkholderia contaminans SK875, a quorum-sensing strain isolated from the swine

Abstract: The Burkholderia cepacia complex (BCC) is a Gram-negative bacterial, including Burkholderia contaminans species. Although the plain Burkholderia is pervasive from taxonomic and genetic perspectives, a common characteristic is that they may use the quorum-sensing (QS) system. In our previous study, we generated the complete genome sequence of Burkholderia contaminans SK875 isolated from the respiratory tract. To our knowledge, this is the first study to report functional genomic features of B. contaminans SK875… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…Most differences were shown in V (37%) and K (27%), respectively. Pan-genome analyses have been steadily conducted for diverse Burkholderia species based on genomics of B. contaminans (Kim et al, 2023) or B. cepacia (Ahmad and Azam, 2020; which showed similar results with ours) and BCC classification (Jin et al, 2020). Recently, Bach et al (2022b) reported a pan-genome focused study that analyzed not only BCC but also B. sensu lato and B. sensu stricto.…”
Section: Pan-genome Analysis For Each Group Of Burkholderiasupporting
confidence: 81%
“…Most differences were shown in V (37%) and K (27%), respectively. Pan-genome analyses have been steadily conducted for diverse Burkholderia species based on genomics of B. contaminans (Kim et al, 2023) or B. cepacia (Ahmad and Azam, 2020; which showed similar results with ours) and BCC classification (Jin et al, 2020). Recently, Bach et al (2022b) reported a pan-genome focused study that analyzed not only BCC but also B. sensu lato and B. sensu stricto.…”
Section: Pan-genome Analysis For Each Group Of Burkholderiasupporting
confidence: 81%